Molecular Diversity and Distribution of Arbuscular Mycorrhizal Fungi at Different Elevations in Mt. Taibai of Qinling Mountain - Zhang, Mengge; Shi, Zhaoyong; Yang, Mei; Lu, Shichuan; Cao, Libing; Wang, Xugang (Frontiers in Microbiology, 2021)
Arbuscular mycorrhizal fungi (AMF) play a vital role in ecosystems, especially in ecosystem variability, diversity and function. Understanding AMF diversity, distribution and their driver at different altitudinal gradients are benefit for understanding the ecological function of AMF in mountain ecosystems. In this study, we explored the AMF molecular diversity and their distribution from 660 to 3500 m a.s.l. in Mount Taibai of Qinling Mountains based on high throughput sequencing technology. A total of 702 operational taxonomic units (OTUs) in 103 species of AMF are isolated from soil samples, which belong to 9 identified and one unidentified genus in 10 Family. The fungi in the genus of Glomus is the most dominant with the occurrence frequency of 100% and the relative abundant of 42.268% and 33.048% on the species and OTU level, respectively. The AMF colonization in root could be simulated by a cubic function with the change of altitudes with the peak and trough at a.s.l. 1170 and 2850 m, respectively. Further, AMF diversity indices including Sob, Shannon diversity and Pielou’s evenness also showed the same cubic function change trends with increasing altitude at OTU and species level. However, the average values of diversity indices at OTU level are always higher than these at the species level. Based on the OTU level, the highest and lowest values of Shannon and Pielou’s indices are observed at the altitudes of 1400 and 2800 m, respectively. The pattern of AMF community distribution in Mt. Taibai is driven by altitude with the characteristics of more abundant in the med-low altitude than high altitude areas. In general, abundant AMF molecular diversity and species exit in different elevations of Mt. Taibai, which indicate gradient changes with elevations.